You can't joke about that : why everything is funny, nothing is sacred, and we're all in this together - Timpf, Kat (Broadside, 2023)
"Comedian Kat Timpf shares how humor has kept her going during the hardest times of her life, and confronts the cancel culture that threatens modern comedy"--